Chapter 1 The Nordic model of digital archiving An introduction - Rostgaard, Marianne (Taylor & Francis, 2024)
The chapter identifies the Nordic countries and describes the Nordic model of digital archiving. We consider what makes Nordic archiving distinctive. Nordic archiving has developed in very close cooperation with public administration, a cooperation that today is more important than ever. Secondly, freedom of information and the rights of citizens to access public records is embodied in the registry system, a cornerstone in Nordic record keeping. Finally, Nordic archivists value pragmatic and predictable solutions and as a result have responded to digital challenges on an ad hoc basis. Nordic digital archiving has developed trustworthy systems for long term preservation of digital records and has started to explore the potential of digital technologies for expanded user access and secondary use or reuse of information or data. International standards and international archival theory are today making their way into Nordic digital archiving, hopefully creating a renewed model of Nordic digital archiving building on the strengths of the Nordic tradition: accountability, transparency and an ideal of archives serving the common good as trusted institutions attending to the interest of the public.